Portrait photograph of an unidentified man (Boston, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Black (photographer):::Photographer:::::::::::: (Black; Boston, MA; United States, 2023)
Portrait photograph of an unidentified man (undated) by Black, 178 Washington Street, Boston MA from the personal collection of Alexander Wheelock Thayer.